Analisis Faktor Kemenangan Pasangan Bobby Nasution & Aulia Rachman pada Pemilihan Walikota Medan - Dennis David Immanuel Damanik; Heri Kusmanto; Hatta Ridho (Universitas Medan Area, 2022)
This article aims to examine the implementation of the 2020 regional head election in Medan City, with the election of Bobby Nasution and Aulia Rachman as mayor and deputy mayor of Medan, the people waiting for promises and solutions for the city of Medan. As the youngest Candidate for Mayor and Deputy Mayor of Medan City, of course there are several factors that became the reason for the people to choose Bobby Nasution – Aulia Rachman as mayor and deputy mayor. It is interesting to study, especially from the voting behavior of the people of the city of Medan in 2020 in selecting the Mayor and Deputy Mayor of Medan. The reason is that the election of the Bobby Nasution-Aulia Rachman pair in the 2020 Medan City Election cannot be separated from how they as a candidate pair attract the public's interest. There are many assumptions that take into account the technicalities and how voters give their choice to the winner of the Medan City Election. The purpose of this study is the Factors Affecting People's Choices in the Victory of the Bobby Nasution - Aulia Rachman Couple in the 2020 Medan Mayor Election. This research method is a qualitative research with descriptive analysis. The results of this study are the presence of voting behavior, appropriate personal branding for the couple Bobby Nasution and Aulia Rachman and motivation.